DEVELOPING PLATFORM FOR STRATEGY BUSINESS SOLUTION THROUGH VALUE CO-CREATION: A STUDY IN PT AUN. (The Indonesian Journal of Business Administration, 2019)
Indonesia enduring expectation to increase realization of foreign investors to Indonesia, in fact the companies have difficulty convincing investors about the ease of investment in Indonesia. Besides that, digitalization brings a change in B2B industry that investors expect fast services and solutions with high accuracy in business reality.For the first three years, the company obtained a rapid growth in business by the large number of foreign investors that invested in manufacturing industry, revenue had  increased more than 20% each year. However, along with weak performance of country's economy, the investor in the manufacturing industry is declining. Investors start complaining regarding the investment and some of investor disappointed for the uncertainly. This condition made the management decide to develop new business strategic. Government create a strategic plan to revitalize manufacture by comply Industry 4.0, this strategic is expected to improve the investment climate with the help of technology.To adapt the technology, the industry players, especially small and medium enterprises are trying to take part in the digital era. It takes initiative from PT AUN management to take an action, company develop sub-business by creating  a bulletin board platform that is connected to the website, presenting news related to business and economy via email. This sub-business is not enough to increase revenue and attract markets to connect with the core business, which is business research and business matching.Through internal and external analysis and the customer approach as a value co-creation, the company is recommended to create an integrated platform between the sub-business and the main business. Strategic formulation using TOWS Matrix, Diamond Strategy and Business model canvas is found out that platform must provide collaboration, the interaction between people and technology and have integration with global industry that aligned with supporting from the government. By  implementing of this strategy, the company is expected to enhance services to its clients, increase the revenue, and creates synergies by collaborating with local and international business players.Keywords: Business Strategy, B2B, Digital Platform, Small and Medium Enterprise (SME), Value Co-Creation.